Lnc‐MEG3 inhibits invasion, migration, and epithelial– mesenchymal transition of nasopharyngeal carcinoma cells by regulating sequestosome 1. Issue 1 (27th October 2021) - Zhou, Caifeng; Cao, Huiling; Meng, Xinyu; Zhang, Qiyao
Abstract: Background: Long non‐coding RNAs regulate malignant behaviors of nasopharyngeal carcinoma (NPC). We aim to investigate the roles and mechanisms of long non‐coding RNA maternally expressed gene 3 (lnc‐MEG3) in NPC. Methods: The expression levels of lnc‐MEG3 and sequestosome 1 (SQSTM1) in NPC tissues and cell lines were detected by quantitative real‐time polymerase chain reaction (qRT‐PCR). Cell invasion and migration abilities were evaluated using transwell and wound healing assays, respectively. Results: Downregulated lnc‐MEG3 expression and upregulated SQSTM1 expression were found in NPC tissues and cells. Overexpression of lnc‐MEG3 inhibited invasion, migration, and epithelial–mesenchymal transition in NPC cells. Overexpression of lnc‐MEG3 reduced the expression level of SQSTM1, and SQSTM1 expression was inversely correlated with lnc‐MEG3 level in NPC tissues. Besides, overexpression of SQSTM1 reversed the effects of lnc‐MEG3 overexpression. Moreover, knockdown of lnc‐MEG3 enhanced NPC progression while its effects were eased by SQSTM1 silence. Conclusion: Lnc‐MEG3 inhibits malignant behaviors by regulating SQSTM1 expression. It may serve as a therapeutic target to treat NPC.